MAXAM-CHIRCHIQ JSC ON PRODUCTION AND ECONOMIC ACTIVITIES FOR 2024 ACTIVITIES FOR THE YEAR 2024 (American Journal of Interdisciplinary Research and Development, 2025)
In this article on the production and economic activities of Maxam-ChircHIQ JSC, the following indicators are presented: the implementation of forecast indicators for the production of the main types of products, the use of production capacities, the production of consumer goods, the technical condition of fixed assets, the development of new types of products, the sale of finished products, export and imports, economic indicators of production, production indicators, production indicators, production indicators, production indicators, production indicators, production indicators, production indicators financial condition, number of personnel, selection and arrangement of personnel and labor protection and safety precautions.